Combined Pars Plana Vitrectomy with Core Vitrectomy with 3600 Barrage Laser and Iris Claw IOL Implantation in Nuclear Drop Case: Video Presentation: Poster Presentation - Case Report - Ophthalmologist - Adityo, Hasiholan Tigor; Tanong, Nicholas Dwiki (Majalah Oftalmologi Indonesia, 2023)
Introduction : Nuclear drop is one of the numerous complications of phacoemulsification surgery. Today, the incidence of nuclear drop has been declining significantly compared to years before. Eyes with nuclear drop tend to have poorer visual and refractive outcome compared to eyes with existing risk factors but no such complication. This video presentation reports a case of nuclear drop with desirable outcome Case Illustration : A 46 years old male patient came with blurry vision on his right eye. Patient was undergone eventful phacoemulsification with nuclear drop complication 2 hours ago. Prior to the admission, visual acuity was 1/300, IOP (Intraocular pressure) 24 mmHg, and retinal evaluation showed there is lens nucleus on the retina. Before admission, the patient was given Methylprednisolone 1x 48mg, Ranitidine 2x150 mg, Ciprofloxacin 2x500mg , Asam mefenamat 3x500mg, Cendo LFX ED 6x1 gtt, Cendo Xytrol ed 6x1 gtt. The patient was planned to do the Pars Plana Vitrectomy followed with 360° barrage laser and Retropupil Iris Claw implantation. One day after the surgery, the visual acuity was 0.2, IOL was well implanted, and no sign of retinal detachment. Four weeks after the surgery, the visual acuity was 0.8 with well implanted IOL Discussion : Conclusion : The outcome of nuclear drop cases is affected by several factors. Preparations before PPV are important to attain a better visual outcome. Until now the optimum time to perform PPV in nuclear drop cases remains undetermined. Meanwhile, rise in IOP indicating no luxury of waiting for PPV